Computational and experimental investigation of the aerodynamics and aeroacoustics of a small wind turbine with quasi-3D optimization. (1st December 2018) - Benim, Ali Cemal; Diederich, Michael; Gül, Fethi; Oclon, Pawel; Taler, Jan
Highlights: IDDES and FH-W models lead to fairly accurate results for wind turbine aeroacoustics. Quasi-3D aerodynamic optimization improves performance of 3D wind turbine blades. Aerodynamic optimization leads to an improved aeroacoustic behaviour. Aerodynamic optimization improves the metrics of psychoacoustics, too. Abstract: Aerodynamics and aeroacoustics of a small horizontal axis wind turbine are investigated experimentally and computationally. The purpose has been to develop a procedure to predict and optimize the aerodynamic and aeroacoustic performance of such turbines. Aeroacoustic measurements are performed by an acoustic camera, while monitoring the plant's power output. In the computational analysis, an unsteady, 3D analysis is applied, modelling the turbulence by the Improved Delayed Detached Eddy Simulation (IDDES), and the aeroacoustics by the Ffowcs Williams and Hawkings (FW-H) approach. In the first part of the study, the original turbine blade is analyzed. A satisfactory agreement between the predictions and measurements is observed for the power conversion efficiency and the emitted sound. In the second part, the aerodynamics of the blade is optimized computationally, in the sense of a Quasi-3D approach, by a previously developed automated procedure. In this part, where a large number of 2D blade profiles are analyzed and optimized, a Reynolds Averaged Numerical Simulation approach is adopted for turbulence. In the third part, it is computationally verified (IDDES, FW-H) that the 3D blade, re-constructed based on the Quasi-3D optimization, exhibits a higher efficiency and lower sound emission. It is shown that the latter holds not only for the overall sound pressure, but also for the criteria pertaining to human perception of sound. Application of high-resolution methods with verification by on-site measurements, demonstration of the proposed Quasi-3D optimization procedure to lead to improved aerodynamic and aeroacoustic performance are innovative aspects of the present investigation. The presented, validated procedure can be applied to predict and improve the aerodynamic and aeroacoustic performance of small horizontal axis wind turbines.